Sabar dan Optimisme dalam Tinjauan Hadis - Suriyati; Muhammad Zulkarnain Mubhar; Siar Ni'mah (Jurnal Penelitian Agama, 2022)
The patience and the optimism are attitudes that must be possessed by a Muslim. However, there are still many who have not implemented it. Both of these attitudes are important to understand well, especially to understand with the hadith of the Prophet. This is because whatever people do must refer to the main guidance, the Qur'an and the hadith of the Prophet. This research is a library research with the thematic approach of hadith. Thematic hadith in this study is mean the themes of the patience and the optimism as the main topics, then conduct a search on the hadiths related to the two. The collection of hadith data related to the patience and the optimism was obtained using the al-maktabah asy-syamilah application. The hadith data found were then analyzed by content analysis. The results of this research on the patience and the optimism are as follows: 1) the discovery of the hadiths about the patience and the optimism in the mu'tabar hadith books, 2) the meaning of the patient and optimism hadith, and 3) understanding the patience and optimism hadith accompanied by its development. These three points are the findings in this study.